2005
DOI: 10.1063/1.2006992
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting properties of ultrathin Bi2Sr2CaCu2O8+x single crystals

Abstract: We use Ar-ion milling to thin Bi2212 single crystals down to a few nanometers or one-to-two (CuO2)2 layers. With decreasing the thickness, superconducting transition temperature gradually decreases to zero and the in-plane resistivity increases to large values indicating the existence of a superconductor-insulator transition in ultrathin Bi2212 single crystals.Comment: 17 pages, 6 figures, to appear in J. Appl. Phys. 98(3) 200

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…Earlier work has found that the two‐dimensional Bi‐2212 with only one unit cell is highly insulating . One of us also studied the thickness dependence of the superconducting properties of ultrathin Bi‐2212 single crystals and found a superconductor–insulator transition when the thickness is lower than 4.5 nm . The lattice vibration wavenumbers in this case will be different from the thick Bi‐2212 crystals or bulk crystals, which may explain the disappearance of the Raman peaks in the 6‐nm‐thick Bi‐2212 flake.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier work has found that the two‐dimensional Bi‐2212 with only one unit cell is highly insulating . One of us also studied the thickness dependence of the superconducting properties of ultrathin Bi‐2212 single crystals and found a superconductor–insulator transition when the thickness is lower than 4.5 nm . The lattice vibration wavenumbers in this case will be different from the thick Bi‐2212 crystals or bulk crystals, which may explain the disappearance of the Raman peaks in the 6‐nm‐thick Bi‐2212 flake.…”
Section: Resultsmentioning
confidence: 99%
“…Electriccal measurements of all fabricated microchips have around the critical temperature as 90 K. Temperature dependence a-b axis resistance also establishes the onset and zero resistance of the microchips. These critical parameters depend on both oxygen level and thickness of the Bi2212 single crystals [20,21]. The thickness of our crystals were changed between 100 and 500 nm because of the uncontrolled cleavege process.…”
Section: Resultsmentioning
confidence: 95%
“…In the literature, many different adhesive materials were used to transfer superconducting crystals on substrate such as silver epoxy (Turkoglu et al 2012;Koseoglu et al 2011), polyimide and non-photosensitive polyimide PIX (Yamada et al 2007;You et al 2005;Wang et al 2001;Yamaki et al 2011). The preference of adhesive can affects response time of bolometer, and the chosen epoxy has to be compatible with temperature cycling.…”
Section: Methodsmentioning
confidence: 99%